21st Century ELT Skills Impact in Students-Teachers Language Learning Process Enhancement - Garcia Mosquera, Maria Fernanda (Coloquio, 2023)
The article addresses a reflective-argumentative text on the 21st century language learning skills significance in the educational process. The study links the paramount outcomes of monitoring techniques, effective communication, and information literacy included in the second-language acquisition by characterizing the advantages of distinctive competencies. Data were retrieved through a bibliographic revision. Findings corroborated that the enjoyment of proper capabilities in the current era constitutes an outstanding factor in the educational process. As a concluding point, it is pivotal to understand the prominent relation between the innovative trends in teaching propensities and the competences of a proactive individual in the present time.